Improving blood glucose in late preterm and small for gestational age infants: the use of dextrose 40% gel - Polo Perucchin, Paola; Aldera, Elena; Calevo, Maria Grazia; De Grande, Bianca; Russo, Monica; Godano, Elisabetta; Maghnie, Mohamad; Arioni, Cesare (Frontiers in Pediatrics, 2025)
IntroductionLimited evidence exists on whether administering oral dextrose gel immediately after birth reduces the risk of hypoglycemia in the early hours of life. The primary objective of this study was to assess whether early administration of 40% dextrose gel in infants with risk factors could reduce the incidence of hypoglycemia during the first few hours after birth. A secondary aim was to evaluate the impact of early dextrose gel administration on breastfeeding outcomes.MethodsThis was a double-arm, randomized trial conducted in two phases that included a total of 297 patients. In the first phase, 200 infants at risk for hypoglycemia were recruited including those who were small for gestational age (SGA), late preterm (LP, born between 34 + 0 and 36 + 6 weeks), large for gestational age (LGA), and infants of diabetic mothers: 100 infants were assigned to the “Dextrose group” and received 40% dextrose oral gel 15 minutes after birth, 100 infants in the “Control group” did not receive any dextrose. Capillary blood glucose was measured at 2 and 4 hours of life. Based on the preliminary findings, the second phase of the study randomized an additional 97 LP infants: 50 in the dextrose group and 47 in the control group, following the same intervention protocol.ResultsIn the first phase, no significant differences in blood glucose levels were found at 2 and 4 hours of life in infants of diabetic mothers or those who were LGA. In SGA infants blood glucose levels tended to decrease significantly between 2 and 4 hours in the control group. In the second phase, LP infants who received dextrose had significantly higher blood glucose at 2 hours compared to those in the control group. Additionally, LP infants in the dextrose group who were breastfed within the first two hours showed significantly higher blood glucose at two hours than those in the control group.DiscussionEarly administration of 40% dextrose gel may be beneficial in maintaining higher blood glucose levels during the first hours of life in LP and SGA infants; our findings suggest that only in LP and SGA patients early intervention with dextrose gel could support glucose homeostasis and potentially improve breastfeeding outcomes.